Intimate partner violence, behaviours associated with risk of HIV acquisition and condom use in married women in Manicaland, East Zimbabwe: An HIV prevention cascade analysis - Alexandra A. Cordeiro; Louisa Moorhouse; Tawanda Dadirai; Rufurwokuda Maswera; Angela Y. Chang; Constance Nyamukapa; Simon Gregson (BMC, 2024)
Abstract Background Intimate partner violence (IPV) is widespread in the WHO African region with generalised HIV epidemics and may contribute to ongoing HIV transmission through its associations with behaviours associated with HIV acquisition risk and low use of prevention methods particularly in marital relationships. Methods We conducted a male condom HIV prevention cascade analysis using data from a general-population survey in Manicaland, Zimbabwe (July 2018-December 2019) to develop an understanding of how interventions that reduce IPV might be built upon to also reduce HIV incidence. Multivariable logistic regression was used to measure associations between currently-married HIV-negative women's experience of IPV and: (1) being in the priority population for HIV prevention methods (i.e. married women engaging in behaviours associated with HIV acquisition risk or with a spouse who engages in similar behaviours or is living with HIV), and (2) male condom use by women in this priority population. Male condom HIV prevention cascades, with explanatory barriers for gaps between successive cascade bars (motivation, access and effective use), were compared for women in the priority population reporting and not reporting IPV. Results We found a positive association between IPV and being in the priority population for HIV prevention methods (72.3% versus 58.5%; AOR = 2.26, 95% CI:1.74-2.93). Condom use was low (< 15%) for women in the priority population and did not differ between those reporting and not reporting IPV. The HIV prevention cascades for women reporting and not reporting IPV were similar; both showing large gaps in motivation and capacity to use male condoms effectively. Women reporting motivation and access to male condoms were more likely to report their partner being a barrier to condom use if they experienced IPV (84.8% versus 75.5%; AOR = 2.25, 95% CI:1.17-4.31). Conclusion The findings of this study support the case for trials of integrated IPV/HIV prevention interventions that are tailored to improve HIV risk perception among HIV-negative married women and to make condom provision more acceptable for this group.